THE RELATIONSHIP BETWEEN DENTAL ARCH DIMENSIONS & INCISAL ABNORMALITIES TO THE MISARTICULATION OF CONSONANTS IN CHILDREN WITH ORAL CLEFTS - Shetty, Amarshree; Rai, Kavita; Hegde, Amitha M.; Dattatreya, T. (Journal of Health and Allied Sciences NU, 2012)
The objective of the present study was to evaluate the association between the dental arch dimensions and the incisal abnormalities or anomalies, to the consonant mis-articulations in children with unilateral cleft palate with the involvement of lip, before and after surgical correction.50 Non-syndromic children with unilateral cleft palate belonging to various experimental groups and 25 non-cleft children (control group) between the age group of 7-9 years were selected for the study. Dental arch dimensions were measured on the dental casts & the selected consonants were evaluated from all the four groups, by 3 qualified speech pathologists and then statistically analyzed. Reduction in the dental arch dimensions was observed in children with untreated cleft palate which further decreased after surgery. The correct production of all the selected consonants /ta/, /da/, /tha/, /dha/, /na/, /na/, /la/, /sa/ and /sha/ which was observed to be 15% in the untreated CP group, improved upto 52.4% after surgical correction in spite of the reduction in the dental arch dimensions. Speech analysis showed a high percentage of distorted sounds were maximum in untreated CP patients which decreased in surgically treated CP patients. Substituted sounds which was found to be absent in untreated cleft palate patients was observed in children who had undergone surgical correction of the palate Conclusion: the reduced arch dimensions and incisal abnormalities may be contributing factors which do not allow 100% normal speech in children with oral clefts.
Keywords: Cleft palate; Dental arch dimensions; Consonant production; Speech